Prediction of internet addiction among high school students in a rural Southern Karnataka, India-A cross-sectional study - S. J. Naresh Kumar; Aaditya Ruhela (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: According to the World Health Organization, there is an explosion in the use of electronic devices, the internet, and gaming platforms. In many countries, it is a significant public health concern, prompting calls to identify adequate public policy. We aimed to investigate the prevalence of internet addiction (IA) among high school students and to assess the relationship between the internet addiction level of high school students and their demographic features with internet use. MATERIALS AND METHODS: A cross-sectional study was conducted among 424 high school children studying in eighth standard-tenth standard. Among 121 public and private high schools listed by the BEO (Block Education Officer) Office in Kolar Taluk four high schools were selected by lottery method from July 2021 to August 2021. The Internet Addiction Test (IAT) by Young was used to assess the intensity of internet usage. RESULTS: The mean IAT score of study participants was 29.6. The mean age of the study population was 14.4 ± 0.84 years. The odds of internet addiction among female students were 4.5 times higher than among male students. The majority (91.5%) of the students had used the internet for educational purpose and the other common reasons for internet usage is social media (43%), entertainment (43%), and gaming purpose (21%). CONCLUSION: The prevalence of IA among high school students is 14.6% with the moderate-risk population was 12.5% and the high-risk population was 2.1%. Students using the internet for both academic and non-academic purposes were more internet addicted. The real challenge is to have control over the usage of social sites-the amount of time being spent and the type of activities adolescents are doing online.